Stabilisation strategies in primary commodity exporting countries: A case study of Chile - Hermann Dick; Egbert Gerken; Thomas Mayer; David P. Vincent (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1982)
A number of recent studies have shown that the short term level of economic activity and employment in primary commodity exporting countries is particularly vulnerable to price fluctuations in world commodity markets. The authorities in such countries, in seeking to maintain output and employment stability, must invoke compensatory macroeconomic adjustment strategies to accommodate both favourable and unfavourable movements in the foreign terms of trade. Chile provides a case in point. Chile has traditionally been heavily reliant on raw materials exports, particularly copper, for its foreign exchange earnings. Copper exports averaged around 70 per cent of total export earnings for the period 1960-19 76. They currently represent about one half of total foreign exchange earnings.
Keywords: 330